Aplicação do ultrassom e compostos químicos na sanitização de couve (brassica Oleracea) - Machado, Maria Clara de Moraes Motta (2017)
Adequate sanitation procedures are essential to ensure the quality and safety of food, making it the main procedure to maintain the microbiological quality of ready-to-eat salads without causing risks to human health. The objective of the study was to evaluate the application of chemical compounds such as sodium dichloroisocyanurate, acetic acid 1000 mg/L, acetic acid 2000 mg/L, peracetic acid 20mg/L, combined or not with 60 kHz ultrasound in the inactivation of adhered Salmonella enterica Typhimurium cells The surface of cabbage butter and the effect of the treatments on the contaminating natural microbiota and on the physical-chemical characteristics of cabbage stored at 7º C for 6 days. In the evaluation of the contaminating natural microbiota the initial count of aerobic mesophiles, filamentous fungi and yeasts and coliforms at 35ºC was 6.8, 5.4 and 3.8 log CFU.g-1 , respectively. After inoculation of Salmonella enterica Typhimurium, the number of cells adhered to the cabbage surface was 6.3 log CFU.g-1. When the cabbage sanitization treatments were applied, the S. Typhimurium count was reduced from 1.6 to 3.8 log CFU.g-1 in relation to the count of non-sanitized samples. For pH, total titratable acidity, soluble solids, mass loss, determination of vitamin C and total phenolic compounds did not show significant changes (p> 0.05) shortly after sanitization and throughout storage. The antioxidant capacity presented a significant reduction throughout the storage. The scanning electron microscopy evidenced the adhesion of S. Typhimurium on the surface of the cabbage and the removal of cells from the sanitization treatments. All treatments performed were equal to or greater than sodium dichloroisocyanurate treatment, indicating that the proposed treatments associated or not with ultrasound have potential for use in the sanitization of cabbage (Brassica oleracea var. acephala).